Water-floating nanohybrid films of layered titanate–graphene for sanitization of algae without secondary pollution. Issue 100 (17th October 2016) - Kim, In Young; Lee, Jang Mee; Hwang, Eui-Ho; Pei, Yi-Rong; Jin, Woo-Bin; Choy, Jin-Ho; Hwang, Seong-Ju
Abstract : A novel efficient and safe methodology to sanitize algae in natural water without secondary pollution is developed by fabricating floating graphene–inorganic hybrid films. Abstract : A novel efficient and safe methodology to sanitize algae in natural water without secondary pollution is developed by fabricating floating graphene–inorganic hybrid films. Two kinds of floating freestanding hybrid films of layered titanate–graphene with efficient algae-killing functionality are fabricated by vacuum-assisted filtration of mixed colloidal suspensions of reduced graphene oxide (rG-O) nanosheets and exfoliated layered titanate nanosheets. Both the titanate nanosheets with lepidocrocite- and trititanate-type structures form homogeneous colloidal mixtures and hybrid freestanding films with rG-O nanosheets. The incorporation of a layered titanate nanosheet enhances the algae-killing activity of the graphene freestanding film, highlighting the beneficial role of photocatalytically-active titanate nanosheet. In comparison to the trititanate nanosheet, the lepidocrocite-type titanate nanosheet is more effective as a building block for enhancing the algae-killing activity of graphene film and for forming a novel nanoblade structure on the surface of the graphene film. The observed high sterilization functionality of the present layered titanate–graphene hybrid films is attributable to both the formation of the novel sharp nanoblade structure and the photocatalytic activity of layered titanate. The present result underscores that hybridization between graphene and photocatalytically-active inorganic nanosheets can provide a powerful way to explore pollution-free recoverable matrix efficient for removing harmful microorganisms in natural water.